The Sexuality Project (Pro-Sex) of the Institute of Psychiatry of the HCFMUSP: first year of activities - Oliveira, Sérgio Ricardo Campanella de; Abdo, Carmita Helena Najjar (São Paulo Medical Journal, 1996)
The results of one year of activities of a multidisciplinary staff comprised of five psychiatrists, one urologist, one gynecologist, and seven psychologists, who integrate the Sexuality Project (PRO-SEX) of the Institute of Psychiatric, Hospital das Clínicas, College of Medicine, University of São Paulo (FMUSP), are presented. Different sexual disorders were evaluated and treated in 140 patients (116 men and 24 women). In addition, a standard protocol was established for the medical assistance of patients; four research projects have been initiated; and courses were offered to residents in psychiatry, urology, and obstetrics-gynecology, as well as to undergraduate and postgraduate students of FMUSP.The PRO-SEX staff presented their research at one congress and two symposiums, and published four articles. Furthermore, an extensive program was established for 1995 in order to continue the advanced medical study of human sexuality.